2016
DOI: 10.3389/fmicb.2016.01445
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Langerhans-Type Dendritic Cells Alters Human Cytomegalovirus Infection and Reactivation in a Stimulus-Dependent Manner

Abstract: Oral mucosal Langerhans cells (LC) are likely to play important roles in host defense against infection by human cytomegalovirus (CMV). We previously showed that in vitro-differentiated immature LC (iLC) populations contain smaller amounts of infected cells but produce higher yields than mature LC (mLC) cultures, obtained by iLC stimulation with fetal bovine serum (FBS), CD40 ligand (CD40L) and lipopolysaccharide (LPS). Here, we sought to determine if exposure to select stimuli can improve LC permissiveness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Differentiated cells were then activated by exposure to GM-CSF, FBS, CD40L and LPS, and infected with CMV strain TB40/E. Consistent with our previously published data [1416], cell numbers did not increase over time (not shown), and only 3 ± 1.5 % of non-activated but 10 ± 5 % of activated cells expressed the viral IE1/IE2 proteins at day two post-infection (pi), notwithstanding the use of a multiplicity of infection (MOI) of ten pfu/cell, which is sufficient to infect the totality of permissive cell types such as fibroblasts (Fig 1A and B). Despite containing higher numbers of IE1/IE2 + cells at each time point, activated cell populations produced lower intracellular progeny amounts per IE1/IE2 + cell than non-activated cells (Fig 1C and D).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Differentiated cells were then activated by exposure to GM-CSF, FBS, CD40L and LPS, and infected with CMV strain TB40/E. Consistent with our previously published data [1416], cell numbers did not increase over time (not shown), and only 3 ± 1.5 % of non-activated but 10 ± 5 % of activated cells expressed the viral IE1/IE2 proteins at day two post-infection (pi), notwithstanding the use of a multiplicity of infection (MOI) of ten pfu/cell, which is sufficient to infect the totality of permissive cell types such as fibroblasts (Fig 1A and B). Despite containing higher numbers of IE1/IE2 + cells at each time point, activated cell populations produced lower intracellular progeny amounts per IE1/IE2 + cell than non-activated cells (Fig 1C and D).…”
Section: Resultssupporting
confidence: 83%
“…In previous studies, we showed that activated and non-activated myeloid cells differentiated from CD34 + HSC are semi-permissive to CMV infection [9, 1416]. As such, they constitute a useful model to identify the cellular determinants of viral tropism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations